Colors of the mind: a meta-analysis of creative arts therapy as an approach for post-traumatic stress disorder intervention - Jiahua Wang; Bo Zhang; Rosliza Yahaya; Azizah binti Abdullah (BMC Psychology)
Abstract Background In clinical practice, creative arts therapy is frequently utilized for the treatment of traumatized adults, with reports of favorable outcomes. However, the effectiveness of this intervention in post-traumatic stress disorder (PTSD) treatment has not yet been definitively established through meta-analysis. In this meta-analysis, we aim to assess the effectiveness of creative arts therapy in the management of PTSD. Methods We conducted systematic literature searches through electronic databases from the extended inception of each database to November 2023. We utilized the Cochrane risk of bias tool to evaluate the quality of evidence. Standardized mean differences (SMDs) were calculated as the effects of creative art therapy on the improvement of PTSD. Results Seven controlled, comparative studies investigated the use of creative arts therapy in treating adults with PTSD. Meta-analysis demonstrated a significant decrease in PTSD symptoms following creative arts therapy (SMD = -1.98, 95% Confidence Interval (CI): -3.8 to -0.16, p < 0.03, I2 = 98%). Subgroup analysis indicates that drama therapy was notably effective, while music, art, and dance/movement therapies exhibited less pronounced effects. Conclusion Despite the limitations, including a limited number of studies, participant size, study heterogeneity, and methodological quality, these results provide valuable understanding regarding the efficacy of creative arts therapies in treating PTSD and highlight the urgent need for additional research in this area.